A Case Study on Collaborative Learning in Promoting Higher Order Thinking Skills (HOTS) among English as a Second Language (ESL) Learners - Zuraina, Ali (Penerbit Universiti Malaysia Pahang, 2009)
This qualitative study explores how collaborative learning experience promotes higher thinking skills among four students in Universiti Malaysia Pahang. Three research questions are posted in the study and these are: How do learners of ESL take responsibility after thinking critically over an issue in collaborative learning? How is it possible for ESL learners in admitting their initial opinion to be incorrect or partially flawed in collaborative learning environment? And what are the strategies that learners of ESL use in working collaboratively after thinking critically over an issue? Several themes are discussed in relation to the research questions stated.